JavaScript for Dummies 4th Edition - Veer, Emily Vander (Wiley Publishing, 2011)
Think of this book as a good friend who started at the beginning, learned the ropes the hard way, and now wants to help you get up to speed. In this book, you can find everything from JavaScript basics and common pitfalls to answers to embarrassingly silly questions (and some really cool tricks, too), all of which I explain from a first-time JavaScript programmer’s point of view. Although you don’t find explanations of HTML in this book, you do find working examples on the companion CD complete with all the HTML you need to understand how JavaScript works.